Analysis of the Potential Utilization of Youtube Websites as a Source of Original Revenue for Tolitoli Regency - Andhy Saputra; Alfansyah Fathur; Hedrat M Nure (Institute of Computer Science (IOCS), 2022)
The Youtube Cooperation Service provides profits that can be used as a source of income. This is an opportunity and potential that can be taken by the government because it is very possible as Youtube's latest regulation related to its Monetization Cooperation program allows all Youtube channels to be Monetized. Tolitoli Regency can take this opportunity as an alternative APBD source. The type of research in this research is descriptive research using quantitative data analysis. This research is expected to provide a specific description and explanation regarding the potential sources of local revenue from Youtube monetization services. The research instrument used is the Youtube revenue calculation system using the Google AdSense payment method and the Blade.com Social site. The data analysis technique used is quantitative data analysis with a descriptive approach, namely determining the potential value of PAD from Youtube monetization as a source of new PAD. The use of the Youtube website as a source of PAD has great potential for the local government of Tolitoli Regency. The estimated local revenue from 1 official Youtube channel of the Tolitoli Regency Government can reach 3,000 USD or Rp. 45,000,000, this amount exceeds the number of PAD realizations in Tolitoli Regency in 2021. The value of this income can continue to increase by improving management and the quality of content. Utilization of the Youtube website through the Youtube monetization program is feasible to be a new source of PAD for Tolitoli Regency.